Cooperative Business Development Model in the Digital Era: A Theoretical Approach - Suparno Suparno; Ari Saptono; Mohammad Sofwan Effendi; Agus Wibowo; Fitra Dila Lestari; Saparuddin Mukhtar; Wang Fei; Kinanti Geminastiti; Rahmatul Khalik; Indri Murniawaty; Bagus Shandy Narmaditya (Universitas Negeri Malang, 2024)
This research aims to develop theoretical prepositions of cooperative business development in the digital era as part of the education and development of cooperatives. The problem studied is the low competitiveness of cooperatives, on the other hand, the high public interest in various cooperative products so modeling solutions is needed in managing cooperatives competitively in the digital era. The cooperative needs to be studied and developed based on superior work performance so that it has a professional management process. This research examines performance theory, with a digital innovation approach. The method used is qualitative with literature and literature studies, theoretically and historically analyzing the development of cooperatives globally and their competitiveness. The results show that employee digital skills, service quality, and member loyalty with active participation predict cooperative business development in the digital era. This study also explains the theoretical measurement factors for future researchers and describes, explains, and measures cooperative business development based on the theoretical study. For future researchers to be able to develop this research empirically with exploratory factor analysis or confirmatory factor analysis, with a wider population and sample. Keywords: Cooperative business, Business development, Digital era, Innovative performance, Service quality